The Impact of Financial Literacy on Investment Decisions: The Moderating Role of Financial Technology - IGN Oka Ariwangsa; Komang Widhya Sedana Putra P; Kadek Wulandari Laksmi P (UPI YPTK Journal of Business and Economics, 2024)
This study investigates the impact of financial literacy on investment decisions and explores the moderating role of financial technology (Fintech). Conducted among small and medium-sized enterprises (SMEs) in Bali Province, Indonesia, the research seeks to understand how financial literacy influences investment choices and how Fintech enhances this relationship. A quantitative approach was used, involving the distribution of questionnaires to 100 SME owners who received business legality through decentralization funds. The data, collected via primary sources and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) 4.0, included measures of financial literacy, investment decisions, and Fintech usage. The findings reveal that higher financial literacy positively impacts investment decisions, with SMEs demonstrating better investment management and decision-making capabilities. Additionally, Fintech was found to strengthen this relationship by providing real-time data and advanced analytical tools that enhance investment decisions for those with strong financial literacy. However, the benefits of Fintech were more significant for individuals with higher financial knowledge, indicating that technology alone cannot replace the need for financial education. This study underscores the importance of integrating financial literacy with technological tools to improve investment outcomes and suggests that future research should explore diverse geographic contexts and longitudinal studies to better understand the evolving dynamics between financial literacy, Fintech, and investment decisions